Nanoparticles in sports garments: a review study - Pedebos, Maria Eduarda; Santos da Rosa, Gabriel; Druzian, Daniel Moro; da Silva, Maurício Dalla Costa Rodrigues; da Silva, William Leonardo; Mortari, Sergio Roberto (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
The present study aims to carry out a lifting, analysis, and description of scientific publications such as articles on nanoparticles in sportswear with the focus on heat control, odor, electricity generation and bacterial infections. Thus, an exploratory search was realized in the ScienceDirect and Scopus from 2019 to Sep 2023. In relation to the production of nanoparticles and fabric, the nanocoating technique is used and can be applied directly to the fabric fiber or with application in the form of a spray on the item of clothing. The application/combination of nanomaterials such as titanium dioxide (TiO2-NPs), silver nanoparticles (Ag-NPs), zinc oxide nanoparticles (ZnO-NPs), and polymer fibers (cellulose diacetate, bacterial cellulose, and polytetrafluoroethylene) allow properties such as antibacterial activity, solar protection and superhydrophobicity to provide breathability, aesthetics, flexibility, and the ability to not cause allergic reactions compared to cotton fabric generally relating the main mechanism to the generation of free radicals and high electronic conductivity.